Mexico - Ganeri, Anita, 1961-; Wright, Rachel; Shackell, John (New York : F. Watts, 1994)
Introduces the geographical, historical, and social aspects of everyday life in Mexico. Includes related craft ideas, games, and activities.
Includes index and glossary.
School Library Journal.
Library Talk.
5.7
5-8
Keywords: Handicraft -- Mexico -- Juvenile literature; Handicraft; Handicraft; Mexico -- Civilization -- 20th century -- Juvenile literature; Mexico -- Social life and customs -- 20th century -- Juvenile literature; Mexico; Mexico; Mexico